Choroidal Structural Changes Assessed with Swept-Source Optical Coherence Tomography after Cataract Surgery in Eyes with Diabetic Retinopathy - Huiping Yao; Sha Gao; Xiaoqing Liu; Yufeng Zhou; Yu Cheng; Xi Shen (Journal of Ophthalmology)
Objective. To determine the influence of phacoemulsification on choroidal vasculature in patients with diabetic retinopathy (DR) undergoing cataract surgery using swept-source optical coherence tomography (SS-OCT). Methods. The study was conducted in 23 eyes of 23 cataract patients with mild/moderate nonproliferative diabetic retinopathy (NPDR) without diabetic macular edema (DME) and 23 age-matched controls. Choroidal thickness (CT) and choroidal vascularity index (CVI) were measured at baseline and 1 week, 1 month, and 3 months after surgery. Results. The baseline CVI in the DR group was significantly lower than that in the control group (P=0.001). CVI in DR patients after surgery significantly increased compared with preoperative values (all P<0.001 for 1 week, 1 month, and 3 months after surgery). Postoperative increase of CVI and CT in the DR group was more than in the control group, and the difference was significant 1 month and 3 months after surgery (all P<0.05). Conclusion. Patients with mild/moderate NPDR have reduced CVI compared with nondiabetic patients at baseline; diabetic cataract surgery tended to induce more increase in CVI and CT as compared with nondiabetic patients. This trial is registered with NCT04499768.